Swedish - Finnish glossary: terms in the Cohabitee Act and law on registered partnership - Language Council of Sweden, Institute for Language and Folklore (Institute for Language and Folklore, 2020)
Swedish - Finnish glossary with terms in the Cohabitee Act and law on registered partnership. Contains 33 entries. 2004.

Swedish - Finnish glossary with terms in the Cohabitee Act and law on registered partnership. Contains 33 terms. 2004.

Svensk-sverigefinsk ordlista med termer i sambolagen och i lagen om registrerat partnerskap. Innehåller 33 uppslagsord. 2004.
Svensk-finsk ordlista: termer i sambolagen och i lagen om registrerat partnerskap
Keywords: marriage; äktenskap; marriage customs; äktenskapsseder; heterosexual relationships; heterosexuella förhållanden; same-sex relationships; samkönade förhållanden; life styles; livsstil; legislation; lagstiftning; Marriage; Äktenskap; law (corpus of rules); lagstiftning; word list; ordlista; Language and linguistics; Språk och lingvistik; Languages and Literature; Språk och litteratur